Effects of different hill spacings and seedling numbers per hill on dry matter production and yield of machine-transplanting hybrid rice - PU Shilin; DENG Fei; HU Hui; ZHONG Xiaoyuan; WANG Li; LI Wu; LI Shuxian; LIAO Shuang; REN Wanjun (浙江大学学报. 农业与生命科学版)
In order to clarify the influence of different hill spacings and seedling numbers on dry matter accumulation and yield formation of machine-transplanting hybrid rice, two different rice varieties, F you 498 and Yixiangyou 2115 were selected as plant materials, and a randomized block experiment with three replicates was conducted to analyze the effects of field collocation pattern on tillers, dry matter production, yield and its component factors of rice. Based on the production practice, the reasonable seedling rate of hybrid rice is 0.42 million per hectare in Sichuan Province, and three field collocation patterns were set as: 1) high hills with low seedlings, 1.5 seedlings transplanted at 30 cm × 12 cm spacing; 2) middle hills with middle seedlings, 2.1 seedlings transplanted at 30 cm × 17 cm spacing; 3) low hills with high seedlings, 2.9 seedlings transplanted at 30 cm × 23 cm spacing. The results showed that the tiller numbers of single hill and population increased first and then decreased with the rice development process. The tiller number of single hill in every development period improved as the hill spacing increased, and the earring- tiller percentage of Yixiangyou 2115 was higher in low hills with high seedlings. The leaf area of single hill and dry matter mass of rice increased as the spacing enlarged, and Yixiangyou 2115 had larger leaf area and dry matter mass of single hill in low hills with high seedlings. Under the three different field collocation patterns, the differences of tiller numbers, dry matter accumulation and transportation, and yield were not significant, which indicated that the decrease of hill numbers per unit area did not influence the productive ear numbers and yield with the same basic seedlings. Reduce hills but not reduce seedlings, and low hills with high seedlings can also achieve high and stable yield.